Social and Political Criticism in the Novel (Shikaju): An Analysis of Genetic Structuralism in Contemporary Arabic Literature - Putri Halimatusa’diah (ASTEEC, 2025)
This article analyzes the narrative structure of Alaa Al Aswany's novel Shikaju (Shikaju) using the genetic structuralism approach developed by Lucien Goldmann. This approach is used to examine the relationship between text structure and the socio-political conditions underlying the creation of the literary work. The research focuses on the dynamics of globalization and acculturation experienced by the characters, particularly in the context of life in Egypt and the United States, which have different social and cultural backgrounds. The results show that the novel's narrative structure reflects a complex identity conflict resulting from the encounter of two different cultures. The characters in the novel experience an identity transformation marked by a tug-of-war between traditional Eastern values and modern Western values. This conflict is not only personal but also reflects broader social realities, such as discrimination against immigrants, stereotypes against Muslims, and an identity crisis amidst globalization. Furthermore, the author's narrative structure demonstrates a close relationship between the characters' individual experiences and the socio-political conditions surrounding them. The novel also reveals the tension between idealism and reality, and shows how the characters attempt to negotiate their identities in stressful situations. Thus, it can be concluded that the novel Shikaju is not only an aesthetic work of literature, but also a critical reflection of the social, cultural, and political dynamics occurring in contemporary global society.